Populační ekologie netopýra vodního Myotis daubentonii - Lučan, Radek (Jihočeská univerzita, 2010)
Various aspects of population ecology of Daubenton?s bat (Myotis daubentonii) were analyzed based on long-term data (1968?1984 and 1999?2009) gathered in a single model study area (ca. 10 km2) in South Bohemia, Czech Republic. Among others, population structure, roosting dynamics, movements between roosts and long-term trends in numbers of bats were described. Results of the study on patterns in reuse of tree cavities suggest that tree cavities may be reused for many consecutive seasons and that this has to be taken into consideration by conservation practices. The results of the study on microclimate of one maternity and one male colony roosting in man-made structures revealed that microclimatic differences may be one of the key factors in roosting preference between the two sexes. Further, a profound effect of changing energetic demands in females during different phases of the reproductive cycle may greatly influence their activity rhytms. In further two studies, the effect of climate on reproductive parameters of bats and abundance of ectoparasitic mites was analyzed. The results suggest that climatic variation greatly influenced reproductive parameters and parasitation of Daubenton?s bats. Last but not least, the seasonal dynamics of parasitation by ectoparasitic mites and the possible effect on bats? condition was analyzed. It was found out that seasonal dynamics in abundance of parasites is adjusted to the reproductive cycle and roosting dynamics of its host.
Population ecology of Daubenton's bat Myotis daubentonii
Keywords: Chiroptera; forest bats; ringing; roosting ecology; bat parasites; climate; global change; Chiroptera; forest bats; ringing; roosting ecology; bat parasites; climate; global change